2013
DOI: 10.1002/pssa.201228759
|View full text |Cite
|
Sign up to set email alerts
|

Electrical characteristics of HfO2 films on InP with different atomic-layer-deposition temperatures

Abstract: The effect of the deposition temperature (200, 250, and 300 8C) on the electrical properties of the atomic-layer-deposited [atomic layer deposition (ALD)] HfO 2 films on InP was studied. A significant grain growth as well as an increase in the accumulation capacitance occurred by increasing the ALD temperature from 200 to 250 8C. However, a further increase to 300 8C degraded the electrical properties as verified by various electrical characterizations, including an accumulation capacitance lowering, a near-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
2
3
0
Order By: Relevance
“…26 Therefore, from the results in this study, a higher D it is expected due to more P-rich oxide formation at higher ALD temperatures. This is consistent with a recent report by An et al, 27 that a significant degradation of electrical performance for HfO 2 /InP stack after ALD at 300 C, compared with that for ALD at 200 and 250 C. In addition, a recent DFT calculation has also suggested that the oxidation of In and P atoms at the (2 Â 4) InP reconstructed surface induces the band gap states. 28 Considering the low growth rate of ALD at 200 C, and the high D it expected from ALD at 300 C, ALD of HfO 2 at 250 C likely the optimum temperature to deposition HfO 2 .…”
Section: Resultssupporting
confidence: 83%
“…26 Therefore, from the results in this study, a higher D it is expected due to more P-rich oxide formation at higher ALD temperatures. This is consistent with a recent report by An et al, 27 that a significant degradation of electrical performance for HfO 2 /InP stack after ALD at 300 C, compared with that for ALD at 200 and 250 C. In addition, a recent DFT calculation has also suggested that the oxidation of In and P atoms at the (2 Â 4) InP reconstructed surface induces the band gap states. 28 Considering the low growth rate of ALD at 200 C, and the high D it expected from ALD at 300 C, ALD of HfO 2 at 250 C likely the optimum temperature to deposition HfO 2 .…”
Section: Resultssupporting
confidence: 83%
“…5 shows C total in accumulation as a function of measurement frequency for our experimental results as well as similar results from the literature. 15,[31][32][33][34] The change in total accumulation capacitance from the lowest to highest measurement frequency for our results is largely consistent with those of the literature. We note that while the substrates and dielectrics used for our comparisons are the same, many of the experimental conditions (e.g., oxide thickness, pre-treatments, annealing conditions) are different.…”
Section: Fitting Of Experimental Data Using the Bt And Digs Modelssupporting
confidence: 92%
“…A crystalline film can contain crystal defects such as crystal faults. In our previous report, we observed that the presence of crystalline defects induce a leakage current through the film and facilitate the soft break down of the HfO 2 film . However, the PDA film showed improved properties in that the SILC level is even maintained at a high electric field region, as shown in Figure c,d.…”
Section: Resultsmentioning
confidence: 80%
“…In our previous report, we observed that the presence of crystalline defects induce a leakage current through the film and facilitate the soft break down of the HfO 2 film. 38 However, the PDA film showed improved properties in that the SILC level is even maintained at a high electric field region, as shown in Figure 10c,d. Finally, from TEM and SILC results, we conclude that a high-quality crystalline HfO 2 film was induced by the PDA process.…”
Section: Resultsmentioning
confidence: 96%